Ideology in postcolonial texts and contexts - Sarkowsky, Katja; Stein, Mark, 1966- (ASNEL paper, 2020)
"Ideology in Postcolonial Texts and Contexts reflects that critiques of ideological formations occur within intersecting social, political, and cultural configurations where each position is in itself 'ideological' - and subject to asymmetrical power relations. Postcolonialism has become an object of critique as ideology, but postcolonial studies' highly diversified engagement with ideology remains a strong focus that exceeds Ideologiekritik. Fourteen contributors from North America, Africa, and Europe focus (I) on the complex relation between postcolonialism, postcolonial theory, and conceptualizations of ideology, (II) on ideological formations that manifest themselves in very specific postcolonial contexts, highlighting the potential continuities between colonial and postcolonial ideology, and (III) on further expanding and complicating the nexus of postcolonial ideology, from veiling as both ideological practice and individual resistance to home as ideological construct; from palimpsestic readings of colonial photography to aesthetics as ideology"--